Programa Minha Casa Minha Vida (2009 2010): Avanços e limites para a população de baixa renda em são Luís MA - Silva, Jadson Pessoa da (2013)
This dissertation makes a reflection on the progress and limits the Minha Casa Minha Vida (MCMV 1) in São Luís - MA, concluded in the period 2009/2010, identifying the main obstacles that present themselves to its implementation in this city, specifically considering its repercussions for the low-income population. We believe that the creation of the MCMV can be considered a step forward for housing policy in Brazil, being the product of the struggles of social movements in search of Urban Reform, anchored in strengthening the Federal Government and social control, checking a huge leap with regard to amount of resources directed to housing finance in the country. In this sense, this paper analyzes the "New National Housing Policy" verifying the role of housing loans under the MCMV Program 1 of the Federal Government as well as the results obtained with reference to the low-income population in São Luís - MA. The literature discusses topics such as housing shortage, urban issues, state and market, housing policies, urban dynamics, focusing on São Luís. Were also conducted documentary research among which we chose to document research, stock reports and pertinent legislation worked in agencies and institutions involved in the formulation of credit policy. The results show that the MCMV Program is an important achievement for the Brazilian housing policy in the sense of having made possible the number of housing units for low income was privileged beyond broad subsidies for this population, something unprecedented in the country. However, following the maintenance of socioeconomic segregation, given the commercial logic of land own the capitalist mode of production, pushing the implementation of the projects the population of lower-income pullets for the city of São Luís, the main limit identified by this work.